Ηλεκτρονικό λεξικό τεχνολογίας & επιστημών : Αγγλοελληνικό -ελληνοαγγλικό. (Αθήνα : Σταφυλίδης)
70.000 λήμματα, 1.800.000 λέξεις.
Windows XP, Windows '95. Windows '98, Windows NT, Windows 2000.
Keywords: Λεξικά -- CD-ROMs.; CD-ROMs.; Τεχνολογία -- Λεξικά -- Ελληνικά -- CD-ROMs.